2019
DOI: 10.1016/j.actbio.2019.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of laminin-1 peptides, VEGF and FGF9 on salivary gland regeneration

Abstract: Hyposalivation is associated with radiation therapy, Sjogren's syndrome and/or aging, and is a significant clinical problem that decreases oral health and overall health in many patients and currently lacks effective treatment. Hence, methods to regenerate salivary glands and restore saliva secretion are urgently needed. To this end, this study describes the modification of fibrin hydrogels with a combination of laminin-1 peptides (YIGSR and A99) and human growth factors (vascular endothelial growth factor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands. Tissue engineering of 3-dimensional (3-D) primary HSG cultures for transplantation into afflicted patients represents another regenerative strategy to restore salivary gland function (Lombaert et al, 2017).…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands. Tissue engineering of 3-dimensional (3-D) primary HSG cultures for transplantation into afflicted patients represents another regenerative strategy to restore salivary gland function (Lombaert et al, 2017).…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…The wounded SMG mouse model was created following a method reported previously [ 49 , 50 , 51 , 52 ]. Briefly, female 6-week-old C57BL/6J mice were anesthetized with 3% ( v / v ) isoflurane with an oxygen flow rate of 2.0 L/min.…”
Section: Methodsmentioning
confidence: 99%
“…Proper vascularisation is essential for endogenous regeneration and for stem cell graft success. While the majority of murine SMG regeneration studies do not report effects on the vascular system, both the drug deferoxamine and laminin-and growth factor-loaded hydrogels improve vascularisation during SMG regeneration [111].…”
Section: Manipulation Of the Stem Cell Niche To Stimulate Regenerationmentioning
confidence: 99%